(3GdWQjb GdSGdc Ydi RHOI GdefGScs - (3GdQMeJj, eUWai Hf eMeO QMeI Gddg Hf YHO GdeMSf, J (B1205 (3g`s
(3ChdgG (B:s
(3hYdi ZjQge HGdJHYjI GdYGWQ Pj GdQGFMI GdYWQI GdfRGgJg hQhfbg Ch dENdGU efTjI jfTC efg QGFMI YWQIs
(3BNQgG (B:s
(3HGdehJ Ydi GdEjeGf Gddge JhafG Ydi GdESdGe hGdEjeGf hSfI SjO GdEfS hGdLGf hGMTQfG aj ReQJg YfO GdejRGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 241s
(3eYLe GdeDdajf (B3 / 880s
(3gOjI GdYGQajf (B2 / 454s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs